REVIEW OF FLIP BARRIER GATE IMPLEMENTATION IN IMPROVING THE QUALITY OF PASSPORT APPLICATION SERVICES IN THE KANTOR IMIGRASI KELAS II NON-TPI KEDIRI - Muhammad Rizqi Ghozhali (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2020)
The practice of brokering is one of the concerns felt by the community at immigration services. The Directorate General of Immigration immediately followed up on the report, and appealed to all technical units of immigration to eradicate brokering practices and the practice of extortion (illegal levies) on immigration services. In line with this appeal, the Directorate General of Immigration made an online application called APAPO. Kantor Imigrasi Kelas II Non-TPI Kediri in follow-up to the practice of extortion and brokering also built the Flip Barrier Gate system. This system utilizes the use of RFID (Radio Frequent Identification) technology embedded in the access card. However, over time, this system began to find some problems. Among the obstacles that have arisen are the inactivity of this system because it is feared that it will become the center of the spread of COVID-19 due to the alternating use of access cards. In this research, development planning is carried out for the Flip Barrier Gate Class II Non-TPI Kediri Immigration Office. Flip Barrier Gate is integrated with APAPO through the use of QR code booking code as an access reader. In development planning, this study uses the system development theory described by Tata Sutabri. This phase consists of 5 stages, namely, system investigation, system analysis, system design, system implementation, system maintenance.